PROBLEMATIKA PENARIKAN PAKSA KENDARAAN BERMOTOR OBYEK JAMINAN FIDUSIA - Paramita, Btari Prajna (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
The forced withdrawal of vehicles that are the object of fiduciary collateral occurs a lot in the community. The attempts at forced withdrawal are sometimes accompanied by acts of violence. In order to avoid security disturbances, the Police at the request of a fiduciary recipient or designated third party are willing to provide security for the forced withdrawal of motorized vehicles on fiduciary collateral objects. What is the problem to be studied is whether the forced withdrawal of fiduciary objects through third party services is in accordance with the law? This research is a normative juridical type which is carried out by examining various formal legal rules such as laws and regulations and theoretical concepts which are then related to problems. From the results of the study it was found that legally the fiduciary recipient was not authorized to carry out the confiscation. In a civil case the authority to carry out a confiscation is the bailiff of the district court. Therefore forced withdrawal or seizure of objects of fiduciary collateral by fiduciary recipients or designated third parties is a vigilante effort, it is not appropriate to obtain police security, if necessary prevented and acted upon.